2016
DOI: 10.1302/0301-620x.98b3.35997
|View full text |Cite
|
Sign up to set email alerts
|

Do trainee surgeons have an adverse effect on the outcome after total hip arthroplasty?

Abstract: This study suggests that when trainees are appropriately supervised, they can obtain results comparable with those of their consultant colleagues when performing THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…Both groups showed excellent improvement within the first year. The results are similar to previous published one-year results after THA 8, 24 . Accordingly, responders as defined by the OMERACT-OARSI criteria 20 were not significantly different in relation to the surgical experience with a responder rate of over 90% in both groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both groups showed excellent improvement within the first year. The results are similar to previous published one-year results after THA 8, 24 . Accordingly, responders as defined by the OMERACT-OARSI criteria 20 were not significantly different in relation to the surgical experience with a responder rate of over 90% in both groups.…”
Section: Discussionsupporting
confidence: 92%
“…However, two different approaches were used in this study - (a) anterolateral, and (b) posterior. In addition, the study reported that a total of 1.5% of the patients developed deep wound infections within the period of ten years after THA 8 . In our study, the overall infection rate after one year of THA was 0.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Second, surgery in public hospitals is often performed by trainee surgeons who may be expected to have a higher rate of revision and this may explain the lower rates of TKR revision in private hospitals when matched for prostheses. Previous research, however, has not shown a higher rate of arthroplasty revision among trainee surgeons …”
Section: Discussionmentioning
confidence: 82%
“…Previous research, however, has not shown a higher rate of arthroplasty revision among trainee surgeons. 8,9 Third, expectations and demands of private patients may differ from public patients. Combined with greater access to care (not just access to consultants and private hospitals, but greater ability to take time off work and arrange for carers), this may increase the rate of revision in the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have evaluated the impact of surgeon grade on the long-term outcome of total hip 20,21 and total knee arthroplasty, 22 to our knowledge, this is the first study which attempts to evaluate the long-term outcome of UKAs performed by trainees. In keeping with the aforementioned studies, our findings suggest that with appropriate training and supervision, trainee surgeons can achieve similar results to experienced consultants during UKA.…”
Section: Discussionmentioning
confidence: 99%